MIC as a quantitative measurement of the susceptibility of Mycobacterium avium strains to seven antituberculosis drugs. - Heifets, L (1988)
MICs of isoniazid, rifampin, ethionamide, streptomycin, amikacin, kanamycin, and capreomycin were determined for Mycobacterium avium complex strains by two methods: broth dilution in 7H12 medium radiometrically and agar dilution on 7H10 agar plates. The broth-determined MICs of all drugs with the exception of isoniazid were two to eight times lower than the agar-determined MICs for most of the tested M. avium strains, which is probably due to the higher absorption and degradation of the drugs in solid media. The MICs, especially those determined in broth, are suggested as quantitative measurements of the degree of susceptibility of M. avium complex strains. For a certain percentage of the M. avium strains the broth-determined MICs were within the limits of MICs found for wild susceptible Mycobacterium tuberculosis strains. These M. avium strains were classified as presumably susceptible. In contrast to M. tuberculosis, the MICs for M. avium strains had a wide range. When the MICs for M. avium strains were only one dilution higher than those for M. tuberculosis, they were tentatively classified as moderately susceptible. The designation moderately resistant or resistant, respectively, is suggested for those M. avium strains for which the MICs were at or above the concentrations achievable in blood. The quantitation of the degree of susceptibility by the MICs and the tentative interpretation of the MICs are suggested for future use in clinical trials as a means of evaluating the patients' responses to chemotherapy compared with the degree of susceptibility of the initial strain isolated before treatment.